SOCIAL ACTORS’ REPRESENTATIONAL ROLE IN POLITICAL HARD NEWS REPORTING: AN APPROACH THROUGH ATTITUDE ANALYSIS - Kazm, Saira; Mohd Noor, Siti Noor Fazelah; Sanif, Sazuliana (ECB, 2023)
The article aimed to explore the meaning lying behind the text by employing Critical Discourse Analysis (CDA) of Norman Fairclough (1995). CDA analysis shows that alternative online Malaysian newspaper was more liberal and gave fair coverage to the ruling as well as opposition political party as compared to a mainstream newspaper. The change in selecting a new government was found based on corruption 1 Malaysia Development Berhad (1MDB) scandal, high cost of living, general service tax, and shifting of loyalties of former BN candidates. The ‘Appraisal analysis’ by Martin and White (2005) had shown that ‘Malaysiakini’ is supporting its ideology by neutral coverage, whereas; ‘The New Straits Times’ had shifted its portrayal from Barisan Nasional (BN) to the existing ruling government of Pakatan Harapan (PH) soon after the results and change of government. Both newspapers have taken the help of external rhetorical markers to support their views. The data set was compiled by selecting five-5 days’ news coverage after elections’ span i.e. 10th to 14th May 2018 by having 1,739 words in total to assess the immediate coverage after the election at the nearest time by employing van Leeuwen’s (2005) socio-semiotic framework by selecting ‘Dr. Mahathir and ‘Najib Razak’ as social actors.